SLÆGTSKAB MED DYR - Tjørnhøj-Thomsen, Tine (Tidsskriftet Antropologi, 2004)
This article discusses the different forms of connections and relatedness between human beings and animals under the heading: Kinship with animals. It is based on an ethnographic study of involuntary childlessness and procreative technologies in Denmark and takes as its starting point the multiple ways childless people make analogies to the animal kingdom when they reflect on and recount their infertility and childlessness. As an example infertile men and women draw analogies to animal reproduction in order to naturalise and legitimise their wish for children, and they compare themselves to experimental animals in order to express their experiences with fertility treatment. Some also refer to their actual relationships with their pets when they consider, for instance, adoption as a solution to their childlessness. The article demonstrates that the ways childless people “think with” and relate to animals are but particular manifestations of a more general Western inclination to integrate pets in human kinship practices and family life. Kinship with animals, however, has its limitation. While pets can be thought of and treated as children and family members, they cannot reproduce personal identity and they cannot connect people in time and ensure genealogical progression and relatedness.